FLUORESCENCE LIFETIME MEASUREMENT OF C5H6 AND C6D6 - Taleb, A. M. (Iraqi Journal of Physics, 2002)
Absorption and lifetime measurements were made for C6H6. and C6D6 molecules in pure solid phase and in solid matrices of Ar, N2, CO, and CO2. All measurement are made at low temperatures ranging between 12-50 K. A modified least square fitting deconvolution was utilized to measure the fluorescence lifetime with an error less than 1%. The results show that the use of matrix isolation technique offer a unique environment that minimize the perturbation of the molecular or atomic system and hence facilitate spectral analysis.